Kompetensi Pedagogik dan Kompetensi Profesionl Guru: Kontribusi Terhadap Peningkatan Hasil Belajar - Finsensius oetpah (Mangifera Edu, 2019)
The prupose of this study was to determine the contribution of pedagogic competence and professional competence of biology teachers of the improvement of student achievement in class x high school in the district of Soe City, South Central Timor District, the sample used was 12 teachear with the criteria of being a civil servant, experienced teaching and certified educators from 6 scholls with he number of school students were 60 students from in 2 parallel classes. The method used in this research is quantitative research with multiple linear analysis using the F test, t test and calculating the simultancous determination cocfficicnt R2 wich is processedusing the SPSSfor windos 16.0 applications. Data collection techniques use questionnaires for teachers and tests for studenst to get primary data. The results showed that the contribution of biology teacher’s pedagogic competence of the first partial correlation with t test showed sig. 0,007 < 0, 05, meaning that pedagogic competence (X1) was constant or influential on learning achievement (Y) and professional kompetence of biology teacher’s on the results of partial correlation second with t test show sig value 0,009 < 0,05 means that professional competence (X2) is constant, or influential on learning achievement (Y), so that the influence of pedagogic competence and professional competence of biology teacher’s together is 70% remaining 30% are other factor not examined by researchers.